(untitled) (Malaysian Journal of Civil Engineering, 2018)
The use of palm oil fuel ash (POFA) as a pozzolanic material for cement replacement in concrete will reduce the cost of concrete and environmental problems. POFA used in this study was ground to increase its degree of fineness to improve its reactivity in the mixture thus enhance the concrete properties. The present study is designed to determine the effect of POFA fineness towards durability of high strength POFA concrete in aggressive environment specifically in terms of increasing its resistance towards chemical attacks namely sulphate, acid and chloride penetration. Two types of mixes were prepared using ash possessing different fineness namely 45 Âµm and 10 Âµm and a control mix with OPC. The entire high strength POFA concrete specimens prepared consist of 20% POFA as partial cement replacement material. Conclusively, integration of POFA as partial cement replacement, especially very fine POFA increase the resistance of high strength POFA concrete in chemical environment towards chloride penetration, acid and sulphate attack .